Prevalence of electrocardiographic changes in Kemerovo region according to the data of the ESSE-RF study - O. M. Polikutina; Yu. S. Slepynina; V. N. Karetnikova; T. A. Mulerova; E. V. Indukaeva; G. V. Artamonova (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the prevalence of ECG changes associated with gender and age according to the program ESSE-RF, Kemerovo.Material and methods. The object of the study is a random sampling of male and female population aged 25-64, Kemerovo. The standard 12-leads ECG was captured in 1623 people. Coding was carried out according to the Minnesota code. The average age of the respondents was 49 years (37; 57), men, 47 years (36; 56), women, 50 years (38; 57), (p=0,004).Results. The ECGs changes were recorded in 265 people (16,3%), in 124 men (17,8%) and 141 women (15,2%) (p=0,159). Heart rhythm disturbances were revealed in 108 people (6,7%), intraventricular conduction disturbances in 147 (9%). The most frequently recorded changes in the T wave (in 11,2% of the subjects), ST segment changes take the second place (in 5,1%), the pathological Q wave was registered less frequently (in 2,5%). In men, the ECG signs of LV hypertrophy, rhythm disturbances, the pathological Q wave were more often detected. In the group of the 50-64-year-olds, the pathological Q wave, changes in ST segment and T wave, rhythm and conduction disturbances were detected significantly more often as well as the greater prevalence of risk factors of ischemic heart disease.Conclusion. Detection of ECG changes is an important stage in the formation of a risk group at the development and progression of the cardiovascular pathology.